THE UNIVERSAL GRAMMAR APPROACH - - Mulyadi (IAIN MADURA, 2012)
This paper describes what Universal Grammar (UG) is, the universal of UG (parameters and principles, marked and unmarked, core and peripheral), UG and L2 Acquisition, Access to UG and L2 Acquisition, the strength and weakness of UG